The Prevalence of Undiagnosed HIV Infection in Those Who Decline HIV Screening in an Urban Emergency Department. (9th May 2011) - Czarnogorski, M.; Brown, J.; Lee, V.; Oben, J.; Kuo, I.; Stern, R.; Simon, G.
Abstract : Objective . To determine the prevalence of occult HIV infection in patients who decline routine HIV testing in an urban emergency department. Design, Setting, and Patients . Discarded blood samples were obtained from patients who had declined routine ED HIV testing. After insuring that the samples came from patients not known to be HIV positive, they were deidentified, and rapid HIV testing was preformed using 5 μ L of whole blood. Main Outcome Measures . The prevalence of occult HIV infection in those who declined testing compared with prevalence in those who accepted testing. Results . 600 consecutive samples of patients who declined routine HIV screening were screened for HIV. Twelve (2%) were reactive. Over the same period of time, 4845 patients accepted routine HIV testing. Of these, 35 (0.7%) were reactive. The difference in the prevalence of HIV infection between those who declined and those who accepted testing was significant (P = .001 ). The relative risk of undetected HIV infection in the group that declined testing was 2.74 times higher (95% CI 1.44–5.18) compared with those accepted testing. Conclusion . The rate of occult HIV infection is nearly three-times higher in those who decline routine ED HIV testing compared with those who accept such testing. Interventions are urgently needed to decrease the opt-out rate in routine ED HIV testing settings.